2005
DOI: 10.1016/j.eja.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of winter wheat in the first 3 years of a monoculture under varying N fertilization in NW Germany

Abstract: Different preceding crops interact with almost all husbandry and have a major effect on crop yields. In order to quantify the yield response of winter wheat, a field trial with different preceding crop combinations (oilseed rape (OSR)-OSR-OSR-wheat-wheatwheat), two sowing dates (mid/end of September, mid/end of October) and 16 mineral nitrogen (N) treatments (80-320 kg N ha −1 ) during 1993/1994-1998/1999, was carried out at Hohenschulen Experimental Station near Kiel in NW Germany. Single plant biomass, tille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
60
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 26 publications
14
60
2
Order By: Relevance
“…Similar results were obtained by Sieling et al (2005), who found that nitrogen fertilization increased the grain yield after all forecrops.…”
Section: Wheat Yieldsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar results were obtained by Sieling et al (2005), who found that nitrogen fertilization increased the grain yield after all forecrops.…”
Section: Wheat Yieldsupporting
confidence: 79%
“…The average grain yield was higher (+0.49 t ha -1 ) in variant where the forecrop was oilseed rape (4.83 -9.98 t ha -1 ), despite the fact that in the control variant (N0) winter wheat grain yields were similar after both forecrops ( were obtained in Germany, where it was found that a higher wheat yield was obtained growing wheat after oilseed rape if compared with variant when wheat was grown after wheat (Sieling et al, 2005). Such a result could be confirmed also by the results of other studies, where oilseed crop in cereal-based cropping systems has shown to have a positive agronomic and economic impacts (Maadi et al, 2012).…”
Section: Wheat Yieldmentioning
confidence: 90%
See 1 more Smart Citation
“…López-Bellido et al (2000) indicated that the inverse relation between kernel weight and N rate is probably due to increase in number of grains per spike and decline in 1000-grain weight prompted by increased N fertilizer rates. Sieling et al (2005) showed that an increased N fertilization compensated for the lower number of ears m -2 and partly reduced the yield losses due to the unfavorable preceding crop combination.…”
Section: Discussionmentioning
confidence: 99%
“…Results from other Czech long-term experiments by Kunzová and Hejcman (2009) and Hejcman and Kunzová (2010) confirmed that grain yields on less productive soils were strongly dependent on N application rates. In addition, Sieling et al (2005) and Hejcman and Kunzová (2010) recorded a statistically significant influence of the preceding crop on grain yield, and Rahimizadeh et al (2010) reported that the preceding crop affects wheat N uptake and use efficiency. This research supports our finding that the preceding crops have a substantial effect on the N response curve (Figure 4).…”
mentioning
confidence: 99%